KESIAPAN PEMERINTAH PROVINSI RIAU DALAM MENCIPTAKAN IKLIM INVESTASI YANG KONDUSIF PADA USAHA MIKRO KECIL MENENGAH DALAM RANGKA MASYARAKAT EKONOMI ASEAN - Suherti, Chintya Okta; Indra, Mexsasai; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In the midst of tumult of democracy and trade access opening urging the Indonesian government took a bold step by signing international trade agreements both at the bilateral, regional and international levels. As we already know with Indonesia is one of the ten countries included in the ASEAN organization. According to mutual agreement, ASEAN shall establish an ASEAN Community in the late 2015's, which consists of three pillars, one of which is the pillar of the ASEAN Economic Community or. The purpose of the establishment of this AEC is that economic integration in ASEAN member countries in the field of trade liberalization in goods, services, investment, capital and labor flows in the region. To that end, formed the ASEAN Comprehensive Investment Agreement (ACIA) in order to create a more liberal investment regime and open. The purpose of this thesis namely; First, to determine the preparation of the Riau provincial government in bringing foreign investors to improve the competitiveness of SMEs in connection with the ASEAN Economic Community; Second, to determine the measures to be taken by the provincial government in connection with the preparation of the SME entrepreneurs increase the ASEAN Economic Community.From the research, there are three main things that can be inferred. First, the government's readiness Provision of Riau in bringing foreign investors to SMEs in connection with the Economic Community (AEC) in 2015 is to implement policies that have been made by the central government are associated with it. Secondly, In welcoming AEC 2015, there are various efforts made the provincial government to SMEs to face the AEC in order not to lose competitiveness with products from other ASEAN member states, among other things by providing loans (bank and non-bank), a grant of equipment to support the products, provide socialization and training to SMEs Riau Province, as well as lift 175 OCFA (Officers Cooperative Field Assistants) in each sub-district / city